Making sense of suicides by school students in Bhutan: documenting a societal dialogue - Pelden, Sonam (Curtin University, 2016)
This research uses a narrative inquiry approach to explore and stage a Bhutanese community dialogue on the recent troubling rise in suicides by school students. Forty-four individual interviews and seven group interviews were conducted. The voices of secondary school students, key policymakers, a parent, school principals, school guidance counsellors, and a Buddhist teacher represent the Bhutanese education community. A community dialogue on suicide is timely and illustrates that collective efforts can generate systemic changes.